2016
DOI: 10.1007/s00107-016-1077-3
|View full text |Cite
|
Sign up to set email alerts
|

Surface densification of acetylated wood

Abstract: The mechanical properties of wood can be improved by compressing its porous structure between heated metal plates. By adjusting the process parameters it is possible to target the densification only in the surface region of wood where the property improvements are mostly needed in applications, such as flooring. The compressed form is, however, sensitive to moisture and will recover to some extent in high humidity. In this study, therefore, acetylated radiata pine was utilised in the surface densification proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…On the other hand, the reduced penetration may have a negative impact on mechanical adhesion. The compressibility of acetylated wood is affected by the decreasing material moisture [ 81 ]. After acetylation, 20 mm-thick (radial) pine ( Pinus radiata D. Don) samples were densified by only 6.9%, compared to 10% for untreated samples.…”
Section: Bonding Acetylated Woodmentioning
confidence: 99%
“…On the other hand, the reduced penetration may have a negative impact on mechanical adhesion. The compressibility of acetylated wood is affected by the decreasing material moisture [ 81 ]. After acetylation, 20 mm-thick (radial) pine ( Pinus radiata D. Don) samples were densified by only 6.9%, compared to 10% for untreated samples.…”
Section: Bonding Acetylated Woodmentioning
confidence: 99%
“…Laine et al (2013b) achieved similar results for surface densified Scots pine at the same treatment temperature. Acetylating wood before densification resulted in a reduction of the set-recovery from 70 to 20% (Laine et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Their tests showed that the post-treatment at higher temperatures and longer durations improved the dimensional stability of the HTM samples, suggesting a permanent fixation of the transversal compression, but also reduced the thermal stability in the same context. Laine et al (2016b) carried out the surface densification test of acetylated radiata pine and mainly focused on the set recovery and hardness improvement of the densified acetylated wood. According to their work, the pre-acetylation significantly reduced the set recovery, and the hardness and the hardness recovery of the acetylated samples increased significantly due to densification.…”
Section: Introductionmentioning
confidence: 99%